TITLE FORM OF ADDRESS ISLAMIC FIGURE IN INDONESIA - Kamal, Mustafa; Hendrokumoro (JURNAL KAJIAN ISLAM MODERN, 2024)
The research discusses the choice of names for Islamic religious figures in Indonesia, because it is motivated by the diversity of nicknames for Islamic religious figures in Indonesia. This research tries to uncover linguistic phenomena in the choice of nicknames. This research uses this research as qualitative research with a descriptive method. This research found various choices of nicknames for Islamic religious figures in various regions in Indonesia. Among them are Kyai, Gus, Ajengan, Abuya in Java, then Tuan Guru, Buya, Tengku in Sumatra and Anre Gurutta and Gurutta in Sulawesi